Effect of Dietary Supplementation of Mineral Mixture on Milk Yield in Crossbred Dairy Cows - Islam, Malik Raies Ul; Shafi, Musarat; Naikoo, Mehrajuddin; Yatoo, Manzoor Ahmad (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
The present front line demonstration (FLD) was laid to assess the impact of supplementing mineral mixture in livestock ration on milk production and subsequent monetary gains. A sample size of 23 dairy cows with average daily yield of 10.75 litres was selected for laying the demonstration. The mineral mixture supplementation over a period of 120 days increased milk production on an average by 1.45 (13.48%) liters per day, fetching an additional income of 1092 Indian rupees per month per animal to the farmer. The results indicate that dietary supplementation of mineral mixture enhance the milk production of dairy animals and help in improving the socio-economic condition of the farmers to some extent.